PTH-094 Indirect treatment comparison of ustekinumab versus other biologics in moderate to severe crohn's disease: a 1-year treatment sequence analysis. (17th June 2017) - Pacou, M; Mesana, L; Gauthier, A; Naessens, D; Sloan, S; Danese, S; Bonovas, S; Abrams, K
Abstract : Introduction: Indirect evidence is needed to better inform decision-makers on the clinical efficacy of ustekinumab in Crohn's disease (CD). Network meta-analyses in CD are challenged by withdrawal trial designs limiting placebo arm transitivity. A treatment sequence analysis was conducted to compare one year efficacy of biologics in CD. Method: A systematic literature review identified randomised controlled trials for induction and maintenance of clinical efficacy evaluating infliximab, adalimumab, or vedolizumab. Separate analyses were conducted for clinical response (Crohn's Disease Activity Index (CDAI) reduction of 100 points) and remission (CDAI under 150) in patients having either failed conventional or anti-TNF therapy. The relative probability of achieving response at the end of induction was multiplied by the conditional probability of maintaining response or remission after one year. End of maintenance placebo-to-placebo rates (only available from ustekinumab trials) were externally imputed using patient data, adjusted for the proportion of responders and remitters at the end of induction in each trial. Analyses were performed in a Bayesian framework to generate posterior distribution probabilities for ustekinumab to perform better than its comparators. Results: In patients who failed conventional therapy, Bayesian probabilities for better remission or response at 1 year with ustekinumab compared to adalimumab or vedolizumab ranged from 51%(OR[CrI]:1.01 [0.40;2.40]) to 97%(OR[CrI]:1.91 [0.96;3.78]). When comparing ustekinumab to infliximab, probabilities ranged from 16%(OR[CrI]:0.41 [0.05;2.13]) to 34%(OR[CrI]:0.69 [0.08;3.73]). In patients who failed anti-TNF therapy, probabilities for better response or remission at 1 year with ustekinumab compared to adalimumab or vedolizumab ranged from 44%(OR[CrI]:0.94 [0.45;1.97]) to 97%(OR[CrI]:1.89 [0.97;3.67]). Conclusion: This novel approach deals with issues of similarity and transitivity and seems most appropriate to compare one year efficacy of biologics in CD. Looking at the entire treatment sequence suggests a higher likelihood of response or remission at year 1 with ustekinumab compared to vedolizumab or adalimumab, with the lower probabilities for remission and versus adalimumab weekly dosing. Disclosure of Interest: M. Pacou: None Declared, L Mesana: None Declared, A Gauthier: None Declared, D Naessens Conflict with: Janssen Pharmaceutica NV, S Sloan Conflict with: Janssen Global Services LLC, S Danese: None Declared, S Bonovas: None Declared, K Abrams: None Declared